Hemodynamics in Doppler ultrasonography - Jongmin Lee (Ultrasonography)
The cardiovascular system operates through complex hemodynamic processes involving pulsatile blood flow, varying viscosity, and the branching architecture of vessels. Interactions between blood flow and the vascular wall, which are characterized by shear and normal stress, along with wall stiffness, are crucial for maintaining vascular health. Doppler ultrasonography is a highly valuable noninvasive tool for assessing these hemodynamic parameters, enabling the measurement of key indices such as blood flow velocity, flow patterns, wall shear stress, and wall stiffness. This paper emphasizes the clinical significance of these indices and methods of measuring them using Doppler ultrasonography while addressing potential challenges. Accurate interpretation of these measurements is vital for reliable cardiovascular diagnostics and effective clinical decision-making.